2023
DOI: 10.14710/ijred.2023.49814
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Grid and Off-Grid Hybrid Power Systems for Application in University Buildings in Nigeria

Abstract: The Nigerian Universities rely on weak and unreliable fossil-based electric grids with diesel engine generators (DEG) as a backup. However, there is a potential to light up the campuses using power systems derived from primary renewable power systems (RPS) like wind turbine (WT) and solar photovoltaic (PV), that can be on or off-grid to improve the energy mix and duration reliably. This study presents the comparative analysis of the optimal hybrid grid and off-grid systems (OGS & OOGS) for serving the dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…On another hand, Regarding the validity of the HOMER model, the software has been widely used and validated by numerous studies, both numerically and experimentally. Several validation studies have demonstrated the capability of HOMER and its use in research projects, while allowing the programmer to compare various design architectures on the basis of their technical and financial merits (Chouaib et al 2017, Alsafasfeh 2015, Barakat et al 2016, Çetinbaş et al 2019, Alshammari et al 2018, Hassane et al 2022, Khamharnphol et al 2023, Diyoke et al 2023, Mahmoudi et al 2023, Ariae et al 2019). Additionally, HOMER has been validated against multiple software and techniques, as for example in the study of Milosavljević et al 2022.…”
Section: Technical and Economic Inputsmentioning
confidence: 99%
“…On another hand, Regarding the validity of the HOMER model, the software has been widely used and validated by numerous studies, both numerically and experimentally. Several validation studies have demonstrated the capability of HOMER and its use in research projects, while allowing the programmer to compare various design architectures on the basis of their technical and financial merits (Chouaib et al 2017, Alsafasfeh 2015, Barakat et al 2016, Çetinbaş et al 2019, Alshammari et al 2018, Hassane et al 2022, Khamharnphol et al 2023, Diyoke et al 2023, Mahmoudi et al 2023, Ariae et al 2019). Additionally, HOMER has been validated against multiple software and techniques, as for example in the study of Milosavljević et al 2022.…”
Section: Technical and Economic Inputsmentioning
confidence: 99%
“…HOMER is a research software used globally as a guide for optimal planning and evaluation of of-grid [18][19][20][21][22] and ongrid [23][24][25][26] energy systems. Based on its reliability, planning consistency, and intuitive interface, many studies have used this software [27][28][29][30][31]. Te 20-year average climate data for solar irradiance [32][33][34] was achieved from the NASA website.…”
Section: Methodsmentioning
confidence: 99%